Comparison of I-Gel and classic Laryngeal Mask Airway in paediatric population: a parallel group study - Sapkota, Shanta; Hamal, Pawan Kumar; Shah Malla, Sadicchya (Journal of Society of Anesthesiologists of Nepal, 2016)
Background: I-gel, the novel Supraglottic airway device, is easier to insert, has improved stability after insertion with reduced tissue compression.The study aims to compare the efficacy of I-gel with classic Laryngeal Mask Airway in the paediatric population. Methods: A randomised parallel group study was done in Department of Anesthesiology, Kanti Children Hospital, Kathmandu for a period of three months. I gel and classic LMA was compared based on leak airway pressure, time of insertion and ease of insertion. Results: Age and weight are comparable among groups. Compared to cLMA, I-gel provides a better leak pressure seal (16.40+-3.42 vs. 23.11+- 6.17 cm of H2O, p 0.027), faster time of insertion (19.42+-4.40 vs. 29.84+-7.70 seconds, p-0.02) and similar ease of insertion (p-0.571). Conclusions: I-gel compared to classic Laryngeal Mask Airway provides better resistance to leak airway pressure, faster time of insertion with comparable ease of insertion.